2018
DOI: 10.3201/eid2408.171883
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Zika and Dengue Viruses through Simple Clinical Assessment, Singapore

Abstract: Dengue virus and Zika virus coexist in tropical regions in Asia where healthcare resources are limited; differentiating the 2 viruses is challenging. We showed in a case–control discovery cohort, and replicated in a validation cohort, that the diagnostic indices of conjunctivitis, platelet count, and monocyte count reliably distinguished between these viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 9 publications
2
39
0
1
Order By: Relevance
“…Dengue and coronavirus disease 2019 (COVID-19) are difficult to distinguish because they have shared clinical and laboratory features. 1, 2 We describe two patients in Singapore with falsepositive results from rapid serological testing for dengue, who were later confirmed to have severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the causative virus of COVID-19.…”
Section: Covert Covid-19 and False-positive Dengue Serology In Singaporementioning
confidence: 99%
“…Dengue and coronavirus disease 2019 (COVID-19) are difficult to distinguish because they have shared clinical and laboratory features. 1, 2 We describe two patients in Singapore with falsepositive results from rapid serological testing for dengue, who were later confirmed to have severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the causative virus of COVID-19.…”
Section: Covert Covid-19 and False-positive Dengue Serology In Singaporementioning
confidence: 99%
“…In the dengue virus, 14-3-3 ε binds to the NS3 protein and prevents RIG-I from translocating to the mitochondrial antiviral signaling (MAVS) protein adapter, thereby blocking antiviral signaling [76]. Liu et al reported 14-3-3 ε as a critical mediator for the relocation of RIG-I from cytosol to mitochondrial-associated MAVS, as it establishes a translocon complex with RIG-I and TRIM25, eventually triggering an antiviral response [78].…”
Section: Role Of 14-3-3 Family In Rna Virusesmentioning
confidence: 99%
“…Additionally, our group has shown that N protein induces apoptosis by reducing the expression level of 14-3-3 θ in the absence of growth factors (serum), which contributes to the accumulation of the phosphorylated N protein in the nucleus [78]. Likewise, coronavirus 2, or COVID-19, originated from China sharing similar demographic profiles, and laboratory and radiological findings with SARS and Middle East respiratory syndrome (MERS) [80].…”
Section: Role Of 14-3-3 Family In Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, it has been found down-regulated in platelets from dengue patients compared to control 18 , as high levels can promote rapid replication and propagation of the virus 19 . Indeed, the platelet count is one of the diagnostic indices used to distinguish between DENV and ZIKV infections 20 . GSN (Gelsolin) binds to the plus ends of actin monomers or filaments.…”
Section: Machine Learning Highlights Potential New Diagnostic Markersmentioning
confidence: 99%